The Origins of Uneven Development: The Indian Subcontinent - Dutt, Amitava Krishna (American Economic Review, 2016)
In the 17th century, the Indian subcontinent (henceforth: India) was not significantly less developed than Britain. But between 1757, when Britain began colonizing India, and 1947, when India gained independence (and British growth had already slowed down), the ratio between British and Indian per capita income increased at least tenfold (Angus Maddison, 1971), and several countries initially less developed than India grew rapidly while India stagnated. The obvious question is: what caused this uneven development? The answer to this question is important for understanding both the roots of India's present economic backwardness and the current division of